The Subcellular Compartmentalization of Arginine Metabolizing Enzymes and Their Role in Endothelial Dysfunction - Chen, Feng; Lucas, Rudolph; Fulton, David (Frontiers in Immunology, 2013)
The endothelial production of nitric oxide (NO) mediates endothelium-dependent vasorelaxation and restrains vascular inflammation, smooth muscle proliferation and platelet aggregation. Impaired production of NO is a hallmark of endothelial dysfunction and promotes the development of cardiovascular disease. In endothelial cells, NO is generated by endothelial nitric oxide synthase (eNOS) through the conversion of its substrate, L-arginine to L-citrulline. Reduced access to L-arginine has been proposed as a major mechanism underlying reduced eNOS activity and NO production in cardiovascular disease. The arginases (Arg1 and Arg2) metabolize L-arginine to generate L-ornithine and urea and increased expression of arginase has been proposed as a mechanism of reduced eNOS activity secondary to the depletion of L-arginine. Indeed, supplemental L-arginine and suppression of arginase activity has been shown to improve endothelium-dependent relaxation and ameliorate cardiovascular disease. However, L-arginine concentrations in endothelial cells remain sufficiently high to support NO synthesis suggesting additional mechanisms. The compartmentalization of intracellular L-arginine into poorly interchangeable pools has been proposed to allow for the local depletion of L-arginine. Indeed the subcellular location of L-arginine metabolizing enzymes plays important functional roles. In endothelial cells, eNOS is found in discrete intracellular locations and the capacity to generate NO is heavily influenced by its localtion. Arg1 and Arg2 also reside in different subcellular environments and are thought to differentially influence endothelial function. The plasma membrane solute transporter, CAT-1 and the arginine recycling enzyme, ASL, co-localize with eNOS and facilitate NO release. This review highlights the importance of the subcellular location of eNOS and arginine transporting and metabolizing enzymes to NO release and cardiovascular disease.